Bio-computational model of object-recognition: Quantum Hebbian processing with neurally shaped Gabor wavelets - Peruš, Mitja; Bischof, Horst; Loo, Chu Kiong (2005)
Theoretical and simulational evidence, as well as experimental indications, are accumulating that quantum associative memory and imaging are possible. We compare these data with biological evidence. since we find them to a significant extent compatible. This paper presents a computationally implementable integrative model of appearance-based viewpoint-invariant recognition of objects. The neuro-quantum hybrid model incorporates neural processing up to VI and quantum associative processing in VI, achieving together an object-recognition result in V2 and ITC. Results of our simulation of the central quantum-like parts of the bio-model, receiving neurally pre-processed inputs, are presented. This part contains our original simulated storage by multiple quantum interference of image-encoding Gabor wavelets done in a Hebbian way, especially using the Griniasty et al. pose-sequence learning rule. (c) 2005 Elsevier Ireland Ltd. All rights reserved.